Soil Chemical Properties of Silver Fir and Spruce Forest Under Different Systems of Silviculture. II-Changes in Soil Phosphorus - Gupta, M. K.; Singh, R. P.; Jha, M. N. (Indian Forester, 1989)
A study was conducted in Picea smithiana (Spruce) and Abies pindrow (Silver fir) forests managed under selection, shelterwood and clearfelled management systems in Kotgarh Forest Division (H.P.) to study the phosphorus behaviour in soils with challge in these systems. Level of soil phosphorus in different sites within the management systems, specific effects of management systems and site conditions. correlation between phosphorus level and soil depth in all conditions of the study, intercorrdation between total and available phospborus were worked out. Soils under selection system were well supplied with phosphorus followed by shelrerwoott and clearfelled systms. In many cases phosphorus level was indfpendent of soil depths as well as total and available forms were also mutually indeptendent of each other. The immobility of the element, biologically mediated uptake, soil pH etc. seemed to have brought about the pattern observed in this study The selection management and good site conditions have maintained better pbosphorus supply. Overall observations clearly indicate low soil phospborus supply in these forests.